Association Between Dietary Inflammatory Index and Sex Hormone Binding Globulin and Sex Hormone in U.S. Adult Females - Liu, Nuozhou; Feng, Ying; Luo, Xinyao; Ma, Xue; Ma, Fang (Frontiers in Public Health, 2022)
Abstract Context It is still unknown whether the dietary inflammatory index is associated with sex hormone and sex hormone binding globulin (SHBG) in adult women. Objective This study examined the association between dietary inflammatory index and sex hormone and SHBG in adult women. Design and Participants This was a cross-secional study. A total of 2372 female participants (age≥20) from the 2015-2016 National Health and Nutrition Examination Survey were enrolled. Dietary inflammatory potential was assessed by dietary inflammatory index (DII) based on 24-h dietary recall. SHBG was assessed using immuno-antibodies and chemo-luminescence, whereas sex hormone was measured by ID-LC-MS/MS. Results The average DII was 0.07±1.69, ranging from -4.38 (most anti-inflammatory) to 4.21 (most pro-inflammatory). After adjusting all covariates, a per-unit DII increase in DII tertile 3 was related to a 12.55nmol/L SHBG decrease referring to DII tertile 1 (P=0.0072). BMI-stratified subgroup analysis revealed that this negative association became more evident in overweight women (β=-7.41, P=0.0112). Another subgroup analysis stratified by perimenopausal period found this negative association remained strong but only existed in women before (β=-8.24, P=0.0013) or during (β=-5.76, P=0.0010) perimenopausal period. Interaction terms were added to both subgroup analyses and found no significant heterogenecity among different BMI or perimenopausal groups (P>0.05). Treshold analyses showed that the association of age with SHBG was an inverted U-shaped curve (inflection point: age=60yrs). Conclusion: A pro-inflammatory diet caused decreased SHBG and total testosterone.. However, more well-designed studies are still needed to validate and verify the causal relationship between DII and sex hormone and SHBG.